The challenge of adolescents' vocational guidance in the context of liquid modernity - dos Santos, Mariana Moura; Luna, Iuri Novaes; Bardagi, Marucia Patta (Revista de ciencias humanas (Florianópolis), 2014)
This paper proposes a discussion on the process of career guidance with adolescents under the perspective of liquid modernity. In this view, the main features of modernity are the ephemerality, the distance and the superficiality of knowledge and understanding of the subjects about the world and about themselves, generated by impediments and lack of stimulus for reflection. This spirit of detachment and disengagement can bring difficulties in planning personal and professional life, either in adolescence or later, precisely because thinking about one's future and make decisions about it implies self-knowledge, perception of stability of certain interests and personal goals and establishing long-term strategies. In this sense, the implications of the characteristics of liquid modernity on the results and in the very conception of the processes of vocational guidance are discussed throughout the text. Adapted from the source document.